Model of competitive mini-hotel project life cycle - Левыкин, Виктор Макарович; Дэвон, Валерия Викторовна (Eastern-European Journal of Enterprise Technologies, 2014)
Having examined the situation in the hotel market of the city of Kharkov (Ukraine), it was found that one of the major shortcomings in the activities of mini-hotels is mediocre attitude towards customers, lack of proper attention and poor services. In this regard, there is the need to create a mini-hotel, the most important mission of which would be a genuine concern for guests and their comfort, as well as providing unique services of the highest class. For the success of this mission, it is necessary to use modern IT-technologies and information systems that support the competitive mini-hotel project life cycle. It must be kept in mind that project implementation depends on many factors, affecting the life cycle phases, with limitations, primarily on cost, time and emerging risks. Without a formalized description of the interrelationship among existing project phases, it is difficult for the customer and the developer of the project to take into account many informal factors. Therefore, the need to improve the competitiveness of mini-hotel was considered, and a mathematical model of the mini-hotel project life cycle, which has a key role in its implementation was developed. The investigation of hotel services in order to develop measures on improving the competitiveness of hotel services was performed. Solving these tasks will ensure the development of advanced forms and methods of effective management of hotel industry enterprises in Kharkov and Ukraine that objectively meets the strategic objectives of socioeconomic development of the country.